Perceiving truth and ceasing doubts what can we learn from 40 years of China's reform and opening-up? - Cai, Fang (Routledge, 2020)
"China has experienced tremendous developmental success since its reform and opening up policy in 1978. What have contributed to China's high-speed economic growth? What lessons can be learnt from China's successful case? What might be the challenges that China would face on its path to a high-income country? These are some critical questions this book addresses. Based on the facts and economic logic, this book briefly narrates the history of China's successful development in the past 40 years and explains why the China's reform and opening-up has boosted the high-speed growth of its economy. Recognizing the change in the stage of economic development, the author reveals the emerging challenges facing China when transitioning from middle-income country to high-income country. He proposes that the country should transit from the demographic dividend to reform dividend to sustain the long-term development. With its scholarly analysis and plain language, this book would not only attract scholars and students in economics and China studies, but also readers interested in the development of Chinese economy"--
Description based on online resource; title from digital title page (viewed on February 28, 2020)
Keywords: Economic development / China